PELATIHAN PEMURNIAN MINYAK JELANTAH MENGGUNAKAN ZEOLITE ALAM TERKATIVASI ASAM BAGI MASYARAKAT WILAYAH TANJUNG GEDONG, JAKARTA BARAT - Fadliah Fadliah; Lisa Samura; Subandrio Soemali; Syamidi Patian (Universitas Trisakti, 2023)
Used cooking oil is an oil that has been used repeatedly in the process of frying food. Repeated use of cooking oil will cause a decrease in the quality of used cooking oil and if consumed will be harmful to health. The decrease in the quality of used cooking oil due to the formation of more double bonds in the structure of used cooking oil causes the oil to be more easily oxidized. The oxidation experienced by used cooking oil causes the quality of used cooking oil to decrease marked by the increasing value of peroxide number, free fatty acid content, water content and acid number of used cooking oil. One of the efforts that can be done to improve the quality of used cooking oil is to add an adsorbent to the used cooking oil. The added adsorbent serves to adsorb the impurities contained in the used cooking oil. One of the adsorbents that can be used is zeolite, zeolite can be used as an adsorbent because of the wide surface area of ​​zeolite which makes it easier for zeolite to adsorb chemical compounds on its surface. To test the quality of the oil can be done by measuring the peroxide number, free fatty acid content, water content and acid number. In this community service, training activities for refining used cooking oil will be carried out to the people of the Tanjung Gedong area, Tomang, West Jakarta. The link between PkM training in refining used cooking oil using natural zeolite for residents of the Tanjung Gedong area, West Jakarta and PkM flagship usakti, namely in the areas of regional development, ecogreen, and alternative energy. Namely using natural materials such as zeolite which is environmentally friendly to improve the quality of used cooking oil.